2014
DOI: 10.2147/ndt.s60034
|View full text |Cite
|
Sign up to set email alerts
|

Generation of superoxide anion radicals and platelet glutathione peroxidase activity in patients with schizophrenia

Abstract: Blood platelets are considered to be a peripheral marker in schizophrenia and other psychiatric disorders. Oxidative stress in schizophrenia may be responsible for changes in platelet metabolism and function; therefore, the aim of this study was to examine and compare the generation of superoxide anions and activity of an antioxidant enzyme (glutathione peroxidase [GPx]) in blood platelets in patients with schizophrenia and healthy subjects. The level of superoxide anions generated in platelets after thrombin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 40 publications
(74 reference statements)
0
9
0
1
Order By: Relevance
“…Ballesteros et al [43] reported significantly lower GSH and higher GSSG levels in the blood of schizophrenia individuals. Dietrich-Muszalska and Kwiatkowska [44] reported that GPx activity decreased by about 67% in the platelets of individuals with schizophrenia compared with the controls.…”
Section: Glutathione Redox Imbalance In Other Neuropsychiatric Diseasmentioning
confidence: 99%
“…Ballesteros et al [43] reported significantly lower GSH and higher GSSG levels in the blood of schizophrenia individuals. Dietrich-Muszalska and Kwiatkowska [44] reported that GPx activity decreased by about 67% in the platelets of individuals with schizophrenia compared with the controls.…”
Section: Glutathione Redox Imbalance In Other Neuropsychiatric Diseasmentioning
confidence: 99%
“…For instance, total antioxidant and glutathione plasma levels are lower in non-medicated, medicated, first-episode as well as chronic SZ patients, 26 , 27 , 28 , 29 in line with the reduced glutathione levels found in the PFC and cerebral spinal fluid of SZ patients 30 , 31 and in post mortem SZ brains, 32 in which abnormal redox-related protein expression has also been found. 33 Furthermore, peripheral levels of ROS are increased, and those of glutathione peroxidase and superoxide dismutase are decreased in SZ patients, 34 , 35 , 36 , 37 , 38 , 39 independent of drug use or disease stage. Hence, both lower levels of antioxidants and higher levels of ROS are core features of the disorder and are not influenced by disease progression or medication use, indicating that redox imbalance is a primary characteristic of the disorder.…”
Section: Sz Is Associated With Redox Imbalancementioning
confidence: 99%
“…However, there are results for both hyperactivity of superoxide dismutase in this disease (Wu et al, 2012 ) and unaltered activity as compared to controls (Raffa et al, 2011 ; Srivastava et al, 2001 ). Results regarding measuring levels of glutation peroxidase (Raffa et al, 2009 , 2012b ; Dietrich-Muszalska and Kwiatkowska, 2014 ) and catalase (Ben Othmen et al, 2008 ; Raffa et al, 2011 , 2012b ) are contradictory. This is covered in more detail in relevant literature reviews (Yao and Keshavan, 2011 ; Wu et al, 2013 ).…”
Section: Oxidative Stress and Schizophreniamentioning
confidence: 99%